Cpl-7, a Lysozyme Encoded by a Pneumococcal Bacteriophage with a Novel Cell Wall-binding Motif - Bustamante, Noemí (American Society for Biochemistry and Molecular Biology, 2010)
Bacteriophage endolysins include a group of new antibacterials reluctant to development of resistance. We present here the first structural study of the Cpl-7 endolysin, encoded by pneumococcal bacteriophage Cp-7. It contains an N-terminal catalytic module (CM) belonging to the GH25 family of glycosyl hydrolases and a C-terminal region encompassing three identical repeats of 42 amino acids (CW_7 repeats). These repeats are unrelated to choline-targeting motifs present in other cell wall hydrolases produced by Streptococcus pneumoniae and its bacteriophages, and are responsible for the protein attachment to the cell wall. By combining different biophysical techniques and molecular modeling, a three-dimensional model of the overall protein structure is proposed, consistent with circular dichroism and sequence-based secondary structure prediction, small angle x-ray scattering data, and Cpl-7 hydrodynamic behavior. Cpl-7 is an ∼115-Å long molecule with two well differentiated regions, corresponding to the CM and the cell wall binding region (CWBR), arranged in a lateral disposition. The CM displays the (βα)(5)β(3) barrel topology characteristic of the GH25 family, and the impact of sequence differences with the CM of the Cpl-1 lysozyme in substrate binding is discussed. The CWBR is organized in three tandemly assembled three-helical bundles whose dispositions remind us of a super-helical structure. Its approximate dimensions are 60 × 20 × 20 Å and presents a concave face that might constitute the functional region involved in bacterial surface recognition. The distribution of CW_7 repeats in the sequences deposited in the Entrez Database have been examined, and the results drastically expanded the antimicrobial potential of the Cpl-7 endolysin.